EFFECT OF OWNERSHIP STRUCTURE, NET PROFIT MARGIN, DEBT TO EQUITY RATIO, CURRENT RATIO TO PROFIT MANAGEMENT AT TRADING SECTOR LISTED ON INDONESIA STOCK EXCHANGE IN 2018-2021 - Putri Meilany Pangaribuan; Nina Purnasari; Anna Maria Adventrina Turnip; Wesly Andri Simanjuntak (SEAN Institute, 2023)
This study aims to prove and analyze the effect of Ownership Structure, Net Profit Margin, Debt To Equity, Current Ratio on Profit Management in trading sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The population in this study were 35 companies listed on the Stock Exchange. Indonesia in 2018-2021. Of the 35 listed companies, 10 sample companies were selected using purposive sampling. The data used in this study is secondary data, by collecting the information needed from idx financial in the form of financial reports for 2018-2021. The results of the research simultaneously with the F test show that the variables are Ownership Structure, Net Profit Margin, Debt to Equity, Current Ratio effect on earnings management.